2013 International Conference on Electromagnetics in Advanced Applications (ICEAA) 2013
DOI: 10.1109/iceaa.2013.6632328
|View full text |Cite
|
Sign up to set email alerts
|

CSI-EPT: A novel contrast source approach to MRI based electric properties tomography and patient-specific SAR

Abstract: -In this paper, we present a novel method (Contrast Source Inversion -Electric Properties Tomography or CSI-EPT) to dielectric imaging of biological tissue using so-called B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Boundary errors regarding the Laplacian may be reduced by considering backward and forward differentiation or by adapting the kernel-size near boundaries. A recent study (39) has introduced a new approach based on Contrast Source Inversion method. This approach is free of assumptions regarding the piece-wise regions and is based on integral representations of the EM field, avoiding derivatives of B þ 1 fields.…”
Section: Discussionmentioning
confidence: 99%
“…Boundary errors regarding the Laplacian may be reduced by considering backward and forward differentiation or by adapting the kernel-size near boundaries. A recent study (39) has introduced a new approach based on Contrast Source Inversion method. This approach is free of assumptions regarding the piece-wise regions and is based on integral representations of the EM field, avoiding derivatives of B þ 1 fields.…”
Section: Discussionmentioning
confidence: 99%
“…MR-Electrical Properties Tomography (EPT) falls in this sense in a completely new category (1). With EPT it is possible to reconstruct electrical properties contrast images at Larmor frequency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), useful for clinical diagnosis (13,14) and radiofrequency (RF) patient safety (15)(16)(17)(18). Instead, at low frequencies (LF, 100 Hz -1 kHz), where other methods like transcranial magnetic stimulations (TMS) and electrocorticography operate (19)(20)(21)(22)(23)(24)(25), knowledge on the relation between electrical conduction and tissue composition is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance electrical properties tomography (MR-EPT) is a non-invasive measurement technique that derives electrical properties (EPs: conductivity σ and permittivity ε) of human tissues from the distribution of transmit and receive radiofrequency (RF) fields of an MR system (Haacke et al, 1991;Katscher et al, 2009). The tissue EPs distribution is not only important for estimation of the specific absorption rate (Balidemaj et al, 2017;Katscher et al, 2009;Voigt et al, 2012;Zhang et al, 2013), but clinical studies have shown its potential as a biomarker in oncology (Balidemaj et al, 2015a(Balidemaj et al, , 2016Kim et al, 2016;Lazebnik et al, 2007;Lee et al, 2022;Mori et al, 2019;Shin et al, 2015;Suh et al, 2021;Tha et al, 2014Tha et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%